How are phraseological units with the semantic component «learning» modified in the English language? - Айкина Т. Ю. Татьяна Юрьевна (2023, 2023)
The article considers one of the most interesting aspects of lexicology – modifications of phraseological units. The units with the semantic component «learning» were sorted out using the Corpus of Contemporary American English. The most widely used ways to change a phraseological unit from the structural-semantic viewpoint were identified and the phraseological units were classified